E-justice [electronic resource] : information and communication technologies in the court system - Cerrillo i Martinez, Agusti; Fabra i Abat, Pere (Information Science Reference, 2009)
"This book presents the most relevant experiences and best practices concerning the use and impact of ICTs in the courtroom"--Provided by publisher.